Dihydroflavonoids as Bioactive Components of Penthorum chinense, a Miao Ethnomedicine, against NAFLD through Bile Acid Metabolism Pathway. Issue 5 (26th April 2022) - Li, Xiaoxi; Li, Yatong; Zhao, Wenwen; Yu, Lan; Hu, Xiaolu; Zhao, Yimeng; Guo, Qiang; Wang, Xing; Wu, Xia
Abstract: Penthorum chinense Pursh. is a traditional herbal medicine of Miao, and its extracts (PCPE) have been used for treatment of liver diseases in the clinic including nonalcoholic fatty liver disease (NAFLD). However, the active components and pharmacological mechanisms of PCPE for treating NAFLD remain unclear. This study aimed to explore potential mechanisms of action through network pharmacology, molecular docking combined with experimental in vitro . A total of five dihydroflavonoids (1 –5 ) with the same parent nucleus of pinocembrin (PCB) from PCPE, were selected as bioactive ingredients and 109 potential targets related to NAFLD were obtained from public databases and literature mining. The core targets related to the bile secretion signaling were selected based on PPI network and KEGG enrichment analysis for exploring the mechanism of PCPE against NAFLD. Molecular docking results showed good interaction between the core targets in bile secretion signaling pathway and the five compounds predicted to be bioactive. With the strong binding activity to retinoid X receptor‐alpha (RXRA) and farnesoid X receptor (FXR) protein, pinocembrin‐7‐ O‐β ‐D‐glucoside (PCBG, the highest content in PCPE) and its metabolite PCB, could significantly increase the expression of RXRA, FXR and bile salt export pump (BSEP) in L02 cells, and significantly decrease the expression of cholesterol 7α‐hydroxylase (CYP7A1) at mRNA and protein levels. This study provided favorable evidence for mechanism of the main dihydroflavonoids of PCPE against NAFLD, and presented a paradigm for the study of ethnomedicine. Abstract :